2010
DOI: 10.1158/1541-7786.mcr-10-0040
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Activating Transcription Factor 3 by Galectin-9 Induces Apoptosis and Overcomes Various Types of Treatment Resistance in Chronic Myelogenous Leukemia

Abstract: Tyrosine kinase inhibitors (TKI) against Bcr-Abl are the first-line therapeutics for chronic myelogenous leukemia (CML). However, the resistance to Bcr-Abl TKIs is induced in leukemic cells not only by loss of sensitivity to TKIs through Bcr-Abl-related molecular mechanisms but also by loss of addiction to Bcr-Abl TK activity by acquiring Bcr-Abl-unrelated additional oncogenic mutations. Therefore, the identification of an additional therapeutic target has been anticipated for achievement of a complete cure an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 31 publications
(37 reference statements)
2
74
0
Order By: Relevance
“…This apoptotic signaling in multiple myeloma was caspase-dependent and was induced by the activation of the MAP kinases JNK and p38 (22,29). Alternatively, Gal-9 induced apoptosis in chronic myelogenous leukemia by inducing Noxa (12). In the present study, Gal-9 increased the levels of cCK18 in NOZ cells, which are sensitive to Gal-9.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…This apoptotic signaling in multiple myeloma was caspase-dependent and was induced by the activation of the MAP kinases JNK and p38 (22,29). Alternatively, Gal-9 induced apoptosis in chronic myelogenous leukemia by inducing Noxa (12). In the present study, Gal-9 increased the levels of cCK18 in NOZ cells, which are sensitive to Gal-9.…”
Section: Discussionsupporting
confidence: 49%
“…Previous findings suggested that Gal-9 suppresses the proliferation of melanoma (11) and chromic myeloid leukemia (12). Regarding the mechanism underlying Gal-9-induced cell growth inhibition in various cancers, Gal-9 induces cancer cell death via an apoptotic signaling pathway (11)(12)(13). This apoptotic signaling in multiple myeloma was caspase-dependent and was induced by the activation of the MAP kinases JNK and p38 (22,29).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations